INTEGRATION OF MATHEMATICAL AND PHYSICAL KNOWLEDGE IN THE TEACHING OF HIGHER MATHEMATICS - Karimova Shalola Musayevna; Valijonova Khusnobod (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
One of the important factors in improving the quality of personnel is the integration of mathematical knowledge with knowledge of physics, chemistry and other natural sciences in the teaching of higher mathematics in higher education institutions trained by engineers, pedagogical educators, technologists, economists. When a new concept or theoretical knowledge is given from higher mathematics, it is important to apply the knowledge in the sciences in order to give examples or demonstrate how to apply their application.